The Role of Cryptography in Secure Message Transmission over Open Communication Channels - Narayan, Sreekanth (Journal of Research in Science and Engineering, 2025)
In an era of digital communication, the security of message transmission over open channels is paramount. Open channels, such as the internet, are vulnerable to cyber threats, including eavesdropping, tampering, and unauthorized access. Cryptography provides the necessary tools to ensure confidentiality, integrity, and authenticity of transmitted messages. This paper explores the fundamental cryptographic techniques employed in secure communications, including symmetric (private key) and asymmetric (public key) encryption, along with the role of digital signatures in authentication. Symmetric cryptography enables efficient encryption using a shared secret key, while asymmetric cryptography provides enhanced security through the use of public and private key pairs. Additionally, digital signatures play a crucial role in verifying the origin and integrity of messages. By analyzing key cryptographic algorithms and secure communication protocols such as SSL/TLS and PGP, this research highlights the indispensable role of cryptography in modern digital security. Furthermore, the paper discusses contemporary challenges in cryptographic implementation, such as quantum computing threats and key management issues, and explores future directions in cryptographic advancements. Through this study, we aim to emphasize the significance of cryptographic methodologies in ensuring secure digital communication and data protection.